Implementation and performance evaluation of multi level pseudo random sequence generator - Hadeer Hussein Ali; Hadi T. Ziboon; Ashwaq Q. Hameed (Institute of Advanced Engineering and Science, 2023)
In this paper, introduce a proposed multi-level pseudo-random sequence generator (MLPN). Characterized by its flexibility in changing generated pseudo noise (PN) sequence according to a key between transmitter and receiver. Also, introduce derive of the mathematical model for the MLPN generator. This method is called multi-level because it uses more than PN sequence arranged as levels to generation the pseudo-random sequence. This work introduces a graphical method describe the data processing through MLPN generation. This MLPN sequence can be changed according to changing the key between transmitter and receiver. The MLPN provides different pseudo-random sequence lengths. This work provides the ability to implement MLPN practically in more than one method such as microcontroller or field programmable gate array (FPGA). In this paper discusses MLPN performance using MATLAB as compared with golden PN sequence generator with different modulation schemes such as binary phase-shift keying (BPSK), quadrature phase-shift keying (QPSK), and quadrature amplitude modulation 16QAM. The simulation results show that MLPN performs almost likely golden PN sequence but sure with advantage its flexibility to change generated MLPN between transmitter and receiver. The MLPN sequence is applicable in the same field of PN sequence applications such as code division multiple access (CDMA), spread spectrum system (SSS), and data scrambling.